Draft Annual Plan 1998-99 Union Territory of Chandigarh - Planning Commission (Planning Commission, 1998)
Chandigarh is a small Union Territory spread over an area of 114 sq. kms., comprising of the city of Chandigarh and only 18 villages. The population as per 1991 Census of this Union Territory is approximately 6.42 lakhs out of which the rural population is only 66,186. The above relfects the predominantly unban character of the Union Territory. In fact, it will not be far wrong to say that it is basically a city-territory. Chandigarh was conceived of as self-contained capital city, a centre for administrative, educational and cultural activities etc., also having light non-polluting industries and sufficient space for commercial development for the requirments of the city.
Finance Department Planning and Evaluation Organisation Chandigarh Administration